2020
DOI: 10.21203/rs.3.rs-39029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“We have a ticking time bomb”: A qualitative exploration of the impact of canine epilepsy on dog owners living in England

Abstract: Abstract Background Idiopathic epilepsy is a common neurological condition in dogs. Previous research has focused on clinical aspects of seizure management in dogs with idiopathic epilepsy with little attention given to the emotional and logistical challenges for their owners. The current study aimed to explore the impacts of owning a dog with idiopathic epilepsy on owner quality of life and lifestyle, using qualitative methods. Methods Owners of dogs with idiopathic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…48 In a recent qualitative study of owners experiences managing a dog with IE, some interviewees expressed feelings of stress and uncertainty regarding their dog's disease process, which sometimes led them to use the internet to perform self-directed research on their dog's condition. 21 perform self-directed research. 49 Although in the Dutch study, vets felt confident in communicating with owners in terms of offering comfort, explaining epilepsy as a diagnosis and its prognosis to owners, 48 the results presented here, where owners considered veterinary education a high priority, combined with recent findings regarding distress and uncertainty in this ownership group, 49 might indicate disparities in the perceived effectiveness of veterinary communication between vets and owners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48 In a recent qualitative study of owners experiences managing a dog with IE, some interviewees expressed feelings of stress and uncertainty regarding their dog's disease process, which sometimes led them to use the internet to perform self-directed research on their dog's condition. 21 perform self-directed research. 49 Although in the Dutch study, vets felt confident in communicating with owners in terms of offering comfort, explaining epilepsy as a diagnosis and its prognosis to owners, 48 the results presented here, where owners considered veterinary education a high priority, combined with recent findings regarding distress and uncertainty in this ownership group, 49 might indicate disparities in the perceived effectiveness of veterinary communication between vets and owners.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only moderate levels of confidence were reported for knowing when to adjust ASD treatment 48 . In a recent qualitative study of owners experiences managing a dog with IE, some interviewees expressed feelings of stress and uncertainty regarding their dog's disease process, which sometimes led them to use the internet to perform self‐directed research on their dog's condition 21 . This supports previous research indicating that companion animal owners who were uncertain regarding recommendations from their veterinary surgeon were more likely to perform self‐directed research 49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owners in the study also reported making significant lifestyle changes due to their dog's epilepsy, including restricting how often they left the house and, in some cases, changing or ceasing their employment. 24 Seizures may also be accompanied by symptoms such as inappropriate urination or aggression. 3 If these symptoms are not controlled, they may cause stress for the owner who has to regularly clean up after their cat or separate themselves, family members or other animals from the cat to avoid injury.…”
Section: Factors Impacting Owner Burden Of Care: Seizure Controlmentioning
confidence: 99%